The Role of HLA-A2 Expression, CYP2E1 Gene Polymorphisms, and Nitrosamine Levels of Nasopharyngeal Carcinoma Patients in Makassar - Nani Iriani Djufri; Irawan Yusuf; Sutji Pratiwi Rahardjo; Abdul Qadar Punagi (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Nasopharyngeal carcinoma is caused by several factors such as infections of Epstein Barr Virus (EBV), it has also been exaggerated by the genetic factors such as, HLA-A2, and environmental factors such as nitrosamines and the presence of polymorphisms of CYP2E1 gene that activates nitrosamines as pro oncogenes. Objective: To analyse the relationship between HLA-A2 expression, gene polymorphisms of CYP2E1 and nitrosamine levels in patients with nasopharyngeal carcinoma in Makassar. Methods: This research is analytic observational with cross-sectional design. Examination of HLA-A2 expression with immunohistochemical methods was conducted, along with genotyping CYP2E1 gene with Polymerase Chain Reaction (PCR) and Restriction Fragment Length Polymorphism (RLFP), and levels of nitrosamines with LCMS (Liquid Chromatography-Mass Spectrometry). There are 70 samples with NPC, with clinical stadium according to AJCC 2010.  Data were also analyzed with SPSS 20 statistical tests and chi-square. Results: There is no significant result found within the expression of HLA-A2 with a clinical stage of Nasopharyngeal Carcinoma (P =0.554). Therefore, there is no significant correlation between the CYP2E1 gene polymorphism with the clinical stage of Nasopharyngeal Carcinoma (P=0.088). Furthermore, there is no significant correlation found between the levels of nitrosamines with clinical stage (P=0.079) and there was no significant relationship between CYP2E1 gene polymorphism and levels of nitrosamines with clinical stage. Moreover, there was no significant relation between the expression of HLA-A2, CYP2E1 gene polymorphism and levels of nitrosamines with a history of smoking. Conclusion: There was no statistically significant correlation between the expression of HLA-A2, CYP2E1 gene polymorphism and levels of nitrosamines to the clinical stage of Nasopharyngeal Carcinoma. However, if the CT genotype and levels of nitrosamines were detected in the samples obtained, then they have an increased progression of 7.2 times greater compared to patients who only had the CT genotype or only detectable levels of nitrosamines.